The Productivity Effects of Adopting Improved Organic Manure Practices in Nepal - Dhakal, Chandra; Escalante, Cesar L. (Frontiers in Environmental Science, 2022)
Owing to farmers’ issues on accessibility and affordability of chemical fertilizers in Nepal, organic manure has been advocated as a more environmentally sustainable fertilizer input alternative. Using the household survey data from Nepal, we analyze the adoption and productivity effects of improved organic manure practices. Our empirical strategy utilizes a recently developed control function approach in the endogenous switching regression model that allows for substantial heterogeneities accounting for the potential self-selection problem due to observables and unobservables. Findings reinforce the crucial role of social capital as farm households’ adoption decisions are significantly influenced by (1) having adopter neighbors or friends, (2) residing in proximity to the market, and (3) gaining easy access to agricultural extension services. Beyond environmental and social considerations, this study establishes economic motivations for the adoption decision. The results show that the adoption of improved organic manure practices increased crop yield by 17 percentage points. These practices did not only result in significantly higher yields among adopting farms, but counterfactual analyses indicate that non-adopting farms would have realized much better yield conditions had they implemented the technology. The study concludes with implications for policies and initiatives to expand the adoption and impacts of improved organic manure practices in Nepal.